Sistema de geolocalização e rastreamento para a plataforma Android - Compass - Machado, Everto Fabio da Silva (2015)
The embedded technology in smart phones with Android operating system is extremely evolved, which includes global positioning system that allows the geographical location of the device. This project, through a literature review and a case study, you want to use these resources to implement the mapping of all customers of a logistics company, in order to build a database able to provide smarter ways to perform control of visits by sales representatives.